Role of Najran University Scholarship Students in the United Kingdom in cultural bridging and civilizational dialog - Talib bin Ahmed Al-Hamami (PLoS ONE, 2026)
This study explores the role of Najran University scholarship students in the United Kingdom in promoting cultural bridging and civilizational dialog. To achieve this objective, a structured questionnaire was designed and administered. The instrument demonstrated high validity and reliability, with a Cronbach’s alpha coefficient of 0.879. The study sample consisted of 59 Saudi scholarship students from Najran University currently studying in the United Kingdom. The questionnaire was distributed during the second semester of the 2024–2025 academic year. Taking into consideration the reported limitations of the study, the analysis revealed that Najran University scholarship students in the United Kingdom actively contribute to cultural bridging and civilizational dialog within academic institutions in their host country. Their engagement extends beyond the university setting, encompassing residential life and community interactions, where they help promote Saudi cultural and civilizational values. Furthermore, they play a vital role in fostering cross-cultural relationships with international peers. Statistical analysis revealed no significant differences and very weak effect sizes in terms of gender, age, marital status, academic level, or field of study. Additionally, the study identified key mechanisms and strategies utilized by Najran University scholarship students to introduce and represent Saudi culture and to foster constructive civilizational engagement within the multicultural context of the United Kingdom.